The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
ICONIP'99. ANZIIS'99 &Amp; ANNES'99 &Amp; ACNN'99. 6th International Conference on Neural Information Processing. Proceedings (
DOI: 10.1109/iconip.1999.845702
|View full text |Cite
|
Sign up to set email alerts
|

Market basket analysis of library circulation data

Abstract: "Market Basket Analysis" algorithms have recently seen widespread use in analyzing consumer purchasing patterns-specifically, in detecting products that are frequently purchased together. We apply the Apriori market basket analysis tool to the task of detecting subject classification categories that co-occur in transaction records of books borrowed from a university library. This information can be useful in directing users to additional portions of the collection that may contain documents relevant to their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This is because one can find all kinds of correlations in a large dataset. Cunningham and Frank [1999] applied the association rules to the task of detecting subject categories that co-occur in transaction records of books borrowed from a university library. A number of techniques are available to support these tasks, including decision trees, the K-means algorithm, the support vector machine, and selforganization maps.…”
Section: Regressionmentioning
confidence: 99%
“…This is because one can find all kinds of correlations in a large dataset. Cunningham and Frank [1999] applied the association rules to the task of detecting subject categories that co-occur in transaction records of books borrowed from a university library. A number of techniques are available to support these tasks, including decision trees, the K-means algorithm, the support vector machine, and selforganization maps.…”
Section: Regressionmentioning
confidence: 99%
“…This is because one can find many different correlations in a large data set. Cunningham and Frank (1999) applied the association rules to the task of detecting subject categories that co-occur in transaction records of books borrowed from a university library. As shown by the aforementioned studies, data mining opens a new window for data analyses.…”
Section: Research Rationalementioning
confidence: 99%
“…Bollen, Nelson, Geisler, & Araujo, 2007) and electronic business (Liu & Shih, 2005;Shih & Liu, 2008). For example, Cunningham and Frank (1999) developed a recommendation system based on the transaction records of books borrowed from a university library. They found that the recommendation system is not only useful to guide users to relevant documents, but also to determine a library's physical layout.…”
Section: Related Work 21 Video Summarization and Recommendationmentioning
confidence: 99%